Milton in popular culture - Knoppers, Laura Lunger; Semenza, Gregory M. Colón, 1972- (Palgrave Macmillan, 2006)
Breathing life into a Milton for the twenty-first century, this cutting-edge collection shows students and scholars alike how Milton transforms and is transformed by popular literature and polemics, film and television, and other modern media.